Dynamics of Soil Water Content Across Different Landscapes in a Typical Desert-Oasis Ecotone - Wang, Guohua; Gou, Qianqian; Hao, Yulian; Zhao, Huimin; Zhang, Xiafang (Frontiers in Environmental Science, 2020)
An understanding of soil water content dynamics is important for vegetation restoration in an arid desert-oasis ecotone under different landscapes. In this study, the dynamics of soil water content under three typical landscapes (i.e., desert, sand-binding shrubland, and farmland shelter woodland) were investigated in the Hexi Corridor, northwest China, during the growing season from 2002 to 2013. The results showed that the soil water content in the deep layers decreased from 20–30% to a stable low level of 3–5% in the desert and shrubland. For the farmland shelter woodland, the soil water content at the deep layers also decreased, but the decrease rate was much smaller than the desert and shrubland. The decrease of soil water content in the deep soil layers among desert–shrubland–woodland was strongly associated with the increase of groundwater depths. The greatest increase of groundwater depths mainly occurred during 2008–2011, while the largest decrease of soil water content took place during the years 2009–2011, with a time-lag in response to increase in groundwater depths. This study provides new insight into the long-term dynamics of soil water content in a typical desert oasis ecotone under different landscape components from the influence of overexploiting groundwater that cannot be inferred from a short-term study. The findings demonstrate that the sharp increase of groundwater depths could be the main reason behind the reduction of soil water content in the clay interlayers, and sustainable development of groundwater resources exploitation is very important for the management of desert-oasis ecotone from a long-term perspective.